2004
DOI: 10.1128/aem.70.12.7185-7191.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Seasonal Variations of Six Bee Viruses in Apis mellifera L. and Varroa destructor Mite Populations in France

Abstract: A survey of six bee viruses on a large geographic scale was undertaken by using seemingly healthy bee colonies and the PCR technique. Samples of adult bees and pupae were collected from 36 apiaries in the spring, summer, and autumn during 2002. Varroa destructor samples were collected at the end of summer following acaricide treatment. In adult bees, during the year deformed wing virus (DWV) was found at least once in 97% of the apiaries, sacbrood virus (SBV) was found in 86% of the apiaries, chronic bee paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

64
456
16
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 435 publications
(555 citation statements)
references
References 28 publications
64
456
16
10
Order By: Relevance
“…BQCV presence in honeybees only and not in Varroa mites is similar to results obtained in France (Tentcheva et al, 2004a) and Hungary (Forgach et al, 2008). Evidence from our and previous studies suggest that Varroa mites might not play a major role in transmitting this virus (Ball and Allen 1988;Carreck et al, 2002;Forgach et al, 2008;Locke et al, 2012;Ribière et al, 2008;Tentcheva et al, 2004a). However, BQCV was detected in Varroa mites from an apiary in Thailand (Chantawannakul et al, 2006) and it was found that Varroa mites can be vectors of BQCV (Ball, 1989;Johns, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…BQCV presence in honeybees only and not in Varroa mites is similar to results obtained in France (Tentcheva et al, 2004a) and Hungary (Forgach et al, 2008). Evidence from our and previous studies suggest that Varroa mites might not play a major role in transmitting this virus (Ball and Allen 1988;Carreck et al, 2002;Forgach et al, 2008;Locke et al, 2012;Ribière et al, 2008;Tentcheva et al, 2004a). However, BQCV was detected in Varroa mites from an apiary in Thailand (Chantawannakul et al, 2006) and it was found that Varroa mites can be vectors of BQCV (Ball, 1989;Johns, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…In this study, a total of eight apiaries tested positive for BQCV of which two of these apiaries also tested positive for N. apis (25% cooccurrence), thus only partly supporting an association between these pathogens. BQCV presence in honeybees only and not in Varroa mites is similar to results obtained in France (Tentcheva et al, 2004a) and Hungary (Forgach et al, 2008). Evidence from our and previous studies suggest that Varroa mites might not play a major role in transmitting this virus (Ball and Allen 1988;Carreck et al, 2002;Forgach et al, 2008;Locke et al, 2012;Ribière et al, 2008;Tentcheva et al, 2004a).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These viruses were detected in 70% and 40% of the colonies, respectively. Although our sample size is rather small, those viruses show similar infection rates with a large-scale survey made at same season in a template climatic region (Tentcheva D, et al, 2004). In contrast, virus surveys of Africanized honey bees performed at a different season in Brazil (Teixeira E W, et al, 2008;Teixeira E W, et al, 2012) showed similar rates for BQCV (37%), lower rates for DWV (20.3%) and the detection of ABPV (27%) and IAPV (25%).…”
supporting
confidence: 65%